C59 HEART RATE AT DISCHARGE AS INDEPENDENT LONG–TERM PREDICTOR OF ALL–CAUSE MORTALITY IN PATIENTS WITH ACS: INSIGHTS FROM THE APULIA PONTE ACS STUDY. (18th May 2022) - Lisi, F; Locuratolo, N; Rutigliano, D; Campanella, C; Mancini, L; Parisi, G; De Gennaro, L; Bonfantino, V; Potenza, A; Sasanelli, P; Scicchitano, P; Barletta, A; et al.
Abstract: Background: Heart rate is able to impact on the prognosis if patients with cardiovascular diseases. The aim of this study was to evaluate the impact of heart rate at discharge of patients with ACS and/or coronary revascularization on long–term follow–up Methods: This was a subanalysis of the PONTE ACS study. The PONTE ACS study is a prospective, longitudinal, cohort study which enrolled patients who were discharged from HUB centres of ASL BARI after coronary revascularization and/or ACS. They underwent clinical evaluation at 30 days, 3, 6 and 1 year–follow–up. The data were collected after including the data in the electronic medical record of the PONTE ACS study. Anthropometric, clinical and pharmacological parameters, instrumental and laboratory examinations were included. Data were computed in order to evaluate the major determinants of all–cause mortality at one–year follow–up. Results: We finally enrolled 2476 patients (77.4% male, mean age: 67.2±12.0 years). Pharmacological treatments were optimized during the follow–up visits. Heart rate at discharge was 65.5 ± 11.3 bpm. At univariate regression analysis, age, systolic and diastolic arterial pressure, body mass index, smoke habit, diabetes, hypertension, high–density lipoprotein and total cholesterol, creatinine, haemoglobin, fasting glycemia, left ventricle ejection fraction, heart rate, use of ACEi/sartans, statins, dual/triple anti–thrombotics were all related to all–cause mortality. Nevertheless, at multivariate Cox regression analysis, age (β coefficient: 0.07117 ± 0.01942, p = 0.0002), history of hypertension (1.4823 ± 0.7476, p = 0.0474), and heart rate (0.04409 ± 0.01278, p = 0.0006) remained related to the primary endpoint. Conclusions: Heart rate confirmed to act as a long–term predictor of all–cause death in patients with ACS.